(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Insulin icodec, the first once-weekly basal insulin analogue, addresses a longstanding barrier to insulin initiation: the burden of daily injections. By binding reversibly to albumin via a C20 fatty diacid chain, icodec achieves a half-life of approximately 196 hours, enabling stable glucose lowering throughout the week from a single subcutaneous dose. Across the ONWARDS phase 3 program, icodec demonstrated at least noninferior, and in several trials statistically superior, glycated hemoglobin (HbA1c) reduction compared with once-daily basal insulin analogues in type 2 diabetes. The hypoglycemia signal was variable across type 2 diabetes trials but consistently and significantly elevated in type 1 diabetes. The prolonged pharmacokinetic profile confers an important limitation: dosing errors carry sustained consequences, and the effects of an administered dose cannot be rapidly reversed. For patients in whom injection burden is the primary barrier to insulin initiation, a once-weekly option may resolve years of clinical inertia. Nevertheless, this is a measured advance. Clinicians must weigh the convenience of weekly dosing against pharmacokinetic inflexibility, a modest but present hypoglycemia signal, and access barriers that may exclude the patients who stand to benefit most. [J Assoc Clin Endocrinol Diabetol Bangladesh, July 2026; 5 (2): e90516]